Selenium-containing D−A−D-type dopant-free hole transport materials for perovskite solar cells. (July 2021) - Fu, Yajie; Sun, Yapeng; Tang, Hao; Wang, Lingyun; Yu, Huangzhong; Cao, Derong
Abstract: A novel selenium-containing D−A−D-type dopant-free hole-transport material with fused dithienobenzoselenadiazole acceptor unit (DTBS ) was designed, synthesized and applied in a perovskite solar cell (PSC). In addition, two dopant-free hole-transport materials were prepared as references with similar structure but different chalcogen elements (O for DTBF and S for DTBT ) being used. The impact of chalcogen atom variation in the dopant-free hole-transport materials on the properties is systematically investigated, such as the physicochemical, electrochemical, morphological feature and photovoltaic properties in PSC. The PSC fabricated with DTBS shows the power conversion efficiency value of 15.09% due to its high fill factor, which is much higher than those with the references (13.31% for DTBF and 11.65% for DTBT ). Moreover, the PSCs fabricated with DTBS without encapsulation are operational with 77.8% performance retention under air condition after 30 days, which is much better than those prepared with doped spiro-OMeTAD (43.6%). The great stability for the DTBS -based PSC may be owing to the excellent thin film morphology and hydrophobicity of DTBS . Our work demonstrates that the selenium-containing organic compounds can act as the dopant-free hole-transport materials in PSC with both high efficiency and long stability being achieved. Graphical abstract: Image 1 Highlights: Selenium-containing dopant-free hole transport material DTBS is designed for PSC. PSC based on DTBS exhibits a high efficiency of 15.09% without dopants. The PSC exhibits encouraging device stability due to high hydrophobicity.